Dialect inheritance and youth identity: an online ethnography study on dialect enthusiasts community on the new media platforms - Mei, Zhixing (Frontiers in Communication, 2024)
Faced with the decline of dialects, the rise of new media platforms has made young dialect enthusiasts an emerging force in maintaining language diversity. They share dialect content through online communities, which not only enhances the visibility of dialects in daily communication, but also strengthens identity recognition characterized by dialects. This article adopts the method of online ethnography to conduct in-depth research on the dialect community in new media platforms, in order to explore the relationship between dialect inheritance and youth identity. Research has found that dialect enthusiasts not only directly use and experience dialects through new media platforms such as WeChat and Bilibili, but also create a new variety of online dialects. They interact online and negotiate to construct dialect knowledge, providing dialect researchers with more comprehensive language materials, while actively participating in the protection, dissemination, and development of dialect culture. This article believes that the activities of young dialect enthusiasts on new media platforms are of great significance for the inheritance of dialects and the construction of a community with a shared future in cyberspace.